Mapeamento de áreas produtoras de sal do Rio Grande do Norte - Lima, Vanessa Karen Pereira de (Universidade Federal Rural do Semi-Árido, 2019)
Salt is considered a natural renewable resource, just like water, it is classified as the first seasoning of society. However, it is a product that becomes abundant, the same has already been considered as a kind of precious commodity and contemplated by various civilizations. Nowadays, it has become the cause of many repercussions, in the economic case and crises in the society, being extracted usually by means of the mineral extraction of rocks containing sodium chlorine and extracted mainly by evaporation of marine water. Regarding salt production, the state of Rio Grande do Norte (RN) is considered the largest salt producer in Brazil, with an average of 95% of the country's salt production. The main objective of this work is to map and characterize all the salt mines of Rio Grande do Norte, identifying the quantity of their productive areas and their size, being industrial or traditional / artisanal, since the importance of salt and its production in RN is certain . For this, it was used as a form of aid for localization and mapping of salinas, Google Earth, a computer program with database in three-dimensional model of the terrestrial globe, a study was also carried out to determine the size of salinas, in case the types of salt pans, where we have the artisanal and industrial salinas. The results obtained resulted in a more complete and specific analysis on the salt producing area of the state and its specifications. The study carried out the mapping and characterization of 27 salinas in the estuarine zone of Rio Grande do Norte, where the main type is the medium size and the one with respect to the municipality that is part of the estuarine zone, the municipality of Mossoró counts on of the state's productive capacity.
Monografia
Keywords: Salinas; Zona estuarina; Capacidade produtiva; Porte; Mapping; Estuarine zone; Productive capacity; Postage; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA